Accounting Regulation Enforcement and Compliance Behavior of Public Companies (gjstudies, 2022)
This research introduces a novel, cross-disciplinary framework for analyzing accounting regulation enforcement by integrating computational game theory, behavioral economics, and network analysis—an approach largely absent from traditional accounting literature. We move beyond conventional compliance modelsby conceptualizing public companies not as isolated actors but as nodes within adynamic, adaptive network where enforcement signals propagate and influence behavior through complex contagion effects. Our methodology employs agent-basedmodeling to simulate the interaction between regulatory bodies and firms under conditions of imperfect information and bounded rationality, incorporating psychological factors such as trust in regulators and perceived fairness of enforcement actions.The study addresses two original research questions: (1) How do non-linear enforcement strategies, including randomized deep-dive audits and reputation-basedtargeting, affect long-term compliance equilibria across different industry networks?(2) To what extent do peer effects and observational learning within inter-firm networks amplify or dampen the impact of regulatory actions on collective compliance behavior? Our simulations, calibrated with data from enforcement actionsover a decade, reveal several counterintuitive findings. First, moderate levels ofenforcement randomness significantly increase overall compliance compared to predictable, rules-based approaches, as firms cannot easily game the system. Second,targeted enforcement on central network nodes yields disproportionate complianceimprovements but risks creating perceptions of unfairness that undermine regulatory legitimacy. Third, we identify a critical threshold of enforcement transparencybeyond which increased disclosure of enforcement rationale paradoxically reducescompliance among firms with low intrinsic motivation, a finding with substantialpolicy implications. This research contributes a new theoretical lens and methodological toolkit for understanding regulation as a complex adaptive system, offeringevidence-based strategies for designing more effective and resilient accounting oversight regimes.